Hb Midnapore [β53(D4)Ala→Val; HBB: c.161C>T]: A Novel Hemoglobin Variant with a Structural Abnormality Associated with IVS-I-5 (G>C) (HBB: c.92+5G>C) Found in a Bengali Indian Family. (2nd September 2016) - Panja, Amrita; Chowdhury, Prosanto; Basu, Anupam
Abstract: We describe a novel C>T substitution at codon 53 of the HBB gene ( HBB : c.161C>T). The proband was a transfusion-dependent β-thalassemia major (β-TM) patient. DNA was extracted and subsequently, DNA sequencing was done to detect the mutations on the HBB gene. Capillary zone electrophoresis (CZE) revealed the presence of an unknown peak. She inherited this mutation from her grandmother through her mother. This mutation exists in cis with the common β 0 mutation IVS-I-5 (G>C) ( HBB : c.92+5G>C). The proband is homozygous for HBB : c.92+5G>C and needs monthly transfusions. On the other hand, her grandmother, mother and sister all possess this novel mutation cis with the heterozygous HBB : c.92+5G>C. They are carriers not thalassemic. This mutation produces the substitution β53(D4)Ala→Val; HBB : c.161C>T, a new structural hemoglobin (Hb) variant. As this variant was identified in a Bengali family from Paschim Midnapore district of West Bengal, India, it has been designated as Hb Midnapore. This variant has now been reported to the HbVar database.